THE VISUAL CAPITAL AND CULTURAL LENS: A STRATEGIC SYNTHESIS OF FINANCE, HERITAGE TOURISM, AND THE HUMANITIES FOR VALUE CREATION AND ETHICAL GOVERNANCE IN THE DIGITAL ART ECONOMY - Kashyap, Vikesh; Bedi, Bhupinderpreet; Berry, Rahul; Walia, Karan; Chakravorty, Pranami; Thankalayam, Sheen; Samuel P, Moby; Kaur, Mandeep (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The accelerated growth of the digital art economy has reshaped the formation, dissemination and commercialization of cultural property. This theoretical essay formulates a transdisciplinary approach that combines finance, heritage tourism, and the humanities to describe how to create value and govern ethically in digital art ecosystems. Basing on the cultural capital theory, the stakeholder theory, institutional theory, and creative economy approaches, the research presents the notion of visual capital as a multidimensional phenomenon that contains the economic, cultural, and symbolic value. The paper theorizes digital platforms as mediating practices that facilitate the interaction of creative finance, heritage-based experiences and humanities-driven interpretation. Such interactions give rise to economic, cultural, and social value, but at the same time, bring up governance issues of intellectual property and cultural commodification as well as the issue of distributing values fairly. An empirical research is offered in the form of a structured conceptual model with propositions that are going to guide future empirical research. It is also relevant to the literature since the study presents a theory-driven, integrative framework and managerial and policy implications on sustainable and ethical digital art ecosystems.